Budaya Organisasi Dan Pengaruhnya Terhadap Perilaku Karyawan Dan Kinerja Organisasi di PT Sasmito - Valensia Marsha Agustin; Maf’ula Nurhidayah; Sentot Imam Wahyono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of organizational culture on employee behavior and its impact on organizational performance at PT Sasmito. Organizational culture is a system of values, norms, and beliefs that guide the actions of all company members. Data was collected through in-depth interviews with several employees and management (HR staff). The findings show that the organizational culture at PT SASMITO is reflected in the values of discipline and commitment to work quality. The organizational culture is applied in moh 5, namely no gambling, no liquor, no drugs, no stealing, no adultery. Interviews revealed that culture can influence employee behavior in carrying out daily tasks.